Non-invasive electrical stimulation of the brain (ESB) modifies the resting-state network connectivity of the primary motor cortex: A proof of concept fMRI study - Alon, G.; Roys, S.R.; Gullapalli, R.P.; Greenspan, J.D. (Brain research, 2011)
An innovative method to obtain fMRI resting-state network maps during non-invasive electrical stimulation of the brain (ESB) was developed and tested. Five healthy volunteers participated in 2 fMRI sessions. In session one, a transcranial direct current stimulator (tDCS) was applied placing the positive electrode (31.5cm2) over the right M1 of the cortex and the negative electrode (31.5cm2) over the left supra-orbital area of the head. In session two, a monophasic pulsed current stimulator (tPCS) was applied using the identical electrode placement. Imaging was performed on a Siemens 3T Tim Trio scanner with a 12-channel head coil. At each session, five consecutive functional scans were obtained: 1) resting-state without stimulation (Rest-1), 2) a motor scan consisting of self-paced, bilateral finger–thumb opposition task, 3) resting-state with ESB (Stim-1), 4) resting-state without stimulation (Rest-2), and 5) resting-state with ESB, replicating Stim-1 (Stim-2). Data were analyzed using AFNI and MATLAB. For motor task fMRI analysis, a general linear model (GLM) determined the voxels in the right and left M1 that were significantly correlated with the motor task paradigm. The resting-state time series from the voxels in the R-M1 were averaged and the resulting time series used as a regressor in a GLM analysis to identify M1 connectivity maps. Connectivity maps were quantified as R2 values, and then combined to give overlap maps for each of the experimental conditions. Fourier analysis determined the energy in the normalized signal average time courses extracted from L-M1 and R-M1 for each of the resting-state scans. Both tDCS and tPCS lowered the R2 values and energy of the averaged time course in the right and left M1 ROI. The effect of the tPCS appeared more pronounced and less variable among subjects. Applying non-invasive ESB during fMRI scanning may down regulate the motor cortex's resting-state network connectivity. ► fMRI resting-state maps were obtained during non-invasive electrical brain stimulation. ► Direct current (tDCS) or pulsed current (tPCS) were applied over primary motor cortex. ► tDCS and tPCS appear to lower the R2 values and amplitude–time integral in M1 bilaterally. ► Anodal stimulation down regulates the motor cortex's resting-state connectivity.